THE PECULIARITY OF TAKING GYMNASTICS CLASSES WITH STUDENT GIRLS - Yuldasheva Jamilakhan Mukhtarovna; Melikhujayeva Noilakhan; Mirzarahimova Muhtasarkhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
statistics show that in women who have been involved in sports, the difference in pelvis width relative to shoulder width decreases over the years. This change in proportion occurs mainly due to the development of the shoulder joint. It has been observed in females that the elbow joint is overwritten and, more often, the legs are X-shaped, more common compared to males. These factors make it difficult to achieve high results in running, jumping, to rely on it for a long time, increasing the likelihood of injury.